Early reduction of serum TARC levels may predict for success of ABVD as frontline treatment in patients with Hodgkin Lymphoma. (November 2017) - Guidetti, A.; Mazzocchi, A.; Miceli, R.; Paterno', E.; Taverna, F.; Spina, F.; Crippa, F.; Farina, L.; Corradini, P.; Gianni, A.M.; Viviani, S.
Highlights: TARC levels significantly decrease after one cycle of ABVD in HL patients. Cut-Off of 800 pg/ml after one cycle allows to identify patients with good prognosis. TARC-1 below 800 pg/ml is associated with PET-2 negativity and higher PFS. Abstract: Background: Many efforts have been made to predict prognosis of newly diagnosed Hodgkin Lymphoma (HL) patients. Objective of this study was to investigate the association between early reduction of Thymus and Activation-Regulated Chemokine after the first ABVD cycle (TARC-1) and prognosis of HL patients. Methods: Serum samples of 116 HL patients were collected at baseline, after every ABVD cycle and during follow-up. The 99th centile of TARC distribution in a group of 156 independent healthy subjects (800 pg/ml) was considered as cut-off for discriminating between abnormal and normal TARC values. Findings: 101 patients out of 116 had baseline TARC above 800 pg/ml (median value 27515 pg/ml (IQR, 11001‐68139)) and were the object of this analysis. TARC-1 significantly decreased to a median value of 556 pg/ml (IQR, 378–977 pg/ml). TARC-1 values below 800 pg/ml were associated with success of therapy (p = 0.0003) and PET-2 negativity (p = 0.001). TARC-1 ≤ 800 pg/ml identified a population with a significantly higher 5-years PFS in the whole cohort (90.1% vs 55.6%; p < 0.0001) and in both subgroups of advanced (p = 0.003) and early stage patients (p = 0.021). At multivariable analysis, TARC-1 was significant independent predictor of PFS (p = 0.0035). Interpretation: Early reduction of TARC serum levels can predict success of treatment, being associated with achievement of interim PET-2 negative and favorable long-term outcome in HL patients receiving ABVD as front-line therapy.